General considerations on the law disobedience for conscience reasons - Mosquera, Susana (Mercurio Peruano, 2016)
This paper attempts to provide a brief description to the concept of conscientious objection through its relationship with the right to freedom of thought, conscience and religion. The proliferation of jurisprudential examples in which the objection appears between the arguments used by the court, gives the appearance that this legal figure had autonomous life; however, the claim to replace the legal mandate by the mandate of conscience, goes through the necessary verification that such mandate of conscience derives from the need to protect its own manifestation of the content of the right to freedom of thought, conscience and religion. The inability to regulate conscientious objection in such a way that would solve the various and varied practical situations in which this figure is manifested, advise avoiding regulatory rigidity, replacing it through a better use of legal tools of the weighting in those cases where the claims of conscience play a fundamental role.